THE ABILITY TO UNDERSTAND MATHEMATICAL CONCEPT OF STUDENTS OF CLASS VII SMPN 3 PEKANBARU THROUGH COOPERATIVE LEARNING MODEL TYPE OF GROUP INVESTIGATION - zulhendrik; Ambiyar; Ishak Aziz (CV. AFDIFAL MAJU BERKAH, 2021)
This studied aims to know whether there was any significant effect ability of understanding mathematical concepts between students using cooperative learning model of Group Investigation (GI) type with students using conventional learning or not in SMP Negeri 3 Pekanbaru. This research was a quasi-experiment; the researcher played a direct role as a teacher in the learning process. Subjects in this study were the eighth grade students of SMP Negeri 3 Pekanbaru, amounting to 66 and the object of this study was an ability of understanding mathematical concepts. Methods used to collect the data of this study were observation, documentation, and testing. In this study, the class meetings were held for six times, one meeting was for a pre test, in which four times of the meeting was carried out with Cooperative Learning model of Group Investigation (GI) type and one meeting was for a post test. The data collected were analyzed using a t test. Based on the analysis of data, it is shown that there are differences in the ability of understanding mathematical concepts between students using cooperative learning model of Group Investigation (GI) type and students using conventional learning in SMP Negeri 3 Pekanbaru. It can be seen from the comparison of to and tt. At the level of 5%, it was indicated that to is more than tt (3.34 > 2.02). Thus it can be concluded that there were significant effect between students using cooperative learning model of Group Investigation (GI) type with students using conventional learning.